Progressive Failure and Fracture Mechanism of Sandstone under Hydraulic-Mechanical Coupling - Yingming Li; Gang Liu; Tao Qin; Zhupeng Jin; Chengxing Zhao; Shunjie Huang (Shock and Vibration)
Hydraulic coupling often leads to progressive rock failure accidents. Mechanical tests were performed over a range of combined pore water pressure and confining pressure stress path conditions to study the progressive failure characteristics of sandstone under hydraulic-mechanical coupling and explore the crack initiation and pore water fracture mechanism. The closure stress and damage stress were determined by the axial deformation stiffness and volume deformation stiffness. The experimental results indicate that confining pressure is the main controlling factor in the crack propagation stage, and pore water pressure enhances crack evolution. With increasing effective confining pressure, the effective peak deviatoric stress strongly increases and the characteristic stress increases linearly. The initiation stress and damage stress decrease with increasing pore water pressure. The moduli in stages I, II, and III are similar to the law of the transverse and radial deformation ratio with notable differences in stage IV. The fracture trend angle was determined by the ratio of axial crack strain and radial crack strain. Compared with the experimental results, the internal cracks in the sandstone samples are mainly type-II cracks, and type-I cracks are also locally present. After stress damage, the cracks expand and extend at an angle close to the real fracture.